Estágios de desenvolvimento gonadal de fêmeas do camarão-barba-ruça (Artemesia longinaris - Decapoda: Penaeidae) - Dumont,Luiz Felipe Cestari (2004)
The stages of gonadal development for the female of "barba-ruça" shrimp (Artemesia longinaris Bate, 1888) were characterized based on histological analysis. Four stages (immature, almost mature, ripe and spawned) were determined according to the structure and arrangement of cells in the ovary. Each stage corresponds macroscopically to a characteristic color, except stages I (immature) and IV (spawned), in which colors are very similar and can be distinguished only microscopically. The chromatic scale varies from white/translucent (stage I), neutral green (almost mature) to dark green (ripe). The mean size of cells was 56.9 µm (±3.5) (stage I), 127 µm (±2.6) (stage II) and 183 µm (±1.91) (stage III). The size frequency of cells was polimodal, and different cell stages were observed in ripe ovary, suggesting the occurrence of multiple spawning. The chromatic scale developed is an important tool for laboratory analysis, and can be easily used to identify the gonadal stages.